ENGARUH FINANCIAL STABILITY, EXTERNAL PRESSURE, FINANCIAL TARGET, NATURE OF INDUSTRY, AUDIT OPINION DAN CHANGE OF DIRECTORS TERHADAP FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD DIAMOND (Studi empiris pada seluruh Perusahaan yang terdaftar di Bursa Efek Indonesia kecuali sektor Perbankan tahun 2014-2016) - Putri Vianggi Dea; Anugerah Rita; A Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to obtain empirical evidence about the effectiveness ofthe fraud diamond in detecting financial statement fraud. This research analyzesthe influence of variable pressure proxied by financial stability, external pressure,financial targets, the opportunity proxied bynature of industry, razionalizationproxied by audit opinion, and the capability to replace any directors proxiesagainst financial statements fraudulent. The sample was a total of 173 of allCompanies listed on the Indonesia Stock Exchange except the Banking sector in2014-2016. The method of determining the sample uses a purposive samplingmethod with certain criteria. Data analysis technicques in this study used multiplelinier regression and classic asumption test which include normality test,multicolonearity, heteroscedasticity, and autocorrelation. The hypothesis wastested using t – statistic and use SPSS version 17.0 as the software for processingthe data. From the test results, there are four variables of financial stability are:Financial Stability, External Pressure, Audit Opinion, and Change Of Directors.Meanwhile, Financial Target and Nature of Industry has no significant impacton financial statement fraud.Keyword : Financial Stability, External Pressure, Financial Target, Nature ofIndustry, Audit Opinion, Change Of Directors, Financial StatementFraud, Fraud Diamond